1961
DOI: 10.1002/cber.19610940510
|View full text |Cite
|
Sign up to set email alerts
|

Darstellung und Eigenschaften monohalogenierter 3‐Keto‐Δ4.6‐dien‐steroide

Abstract: Ausgehend von 3-Keto-A4.6-dien-steroiden, wurde die Darstellung von in 2a-, 4-oder 6-Stellung monohalogenierten 3-Keto-A4.6aien-steroiden und 2a-bzw. 6-Methoxy-3-keto-A4.a-dien-steroiden und Umwandlungsprodukten derselben beschrieben. Die in 2a-bzw. 4-Stellung halogenierten Verbindungenwurden dabei zum Teil durch Iiberraschende Umlagerungsreaktionen aus 6-Halogeniden erhalten. Die magnetischen Kernresonanzspektren der neuen Verbindungen werden besprochen.Bislang wurden in der Literatur folgende, an den Ringen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Three of the four oxygen atoms of virone were present as 1 700 cm-'; 6, 209.1) is located in a COMe group (6,(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), suggesting a pregnan-20-one skeleton.…”
Section: IImentioning
confidence: 99%
“…Three of the four oxygen atoms of virone were present as 1 700 cm-'; 6, 209.1) is located in a COMe group (6,(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), suggesting a pregnan-20-one skeleton.…”
Section: IImentioning
confidence: 99%
“…[170][171] (2 H, s, 21-H2), 3.65 (1 H, br s, w+ 8 Hz, 7-H), 1.71 (3 H, 4 2 Hz, 2-H), 5 . 0 -6P,7a-Diazido-9a-jluoro-l6a-methyl-3,20-dioxopvegna-1,4diene-1 1 p, 1 7a,2 1 -trio1 2 1 -Acetate ( 14). *-In a manner similar to that described above, reaction of 9~x-fluoro-16a-methyl-3,20-dioxopregna-l,4,6-triene-l lp,l7a,21-triol 21-acetate (12) (432 mg, 1 mmol) with lead tetra-acetate (886 mg, 2 mmol) and trimethylsilyl azide (1.06 ml, 8 mmol) gave, after column chromatography on silica gel, 6p,7 a-diazid0-9a-fluoro-16amethyl-3,20-dioxopregna-l ,4-diene-1 lp,l7a,21-triol 21-acetate (14) (100 rng, 19%), crystallised from ether (52 mg), m.p.…”
mentioning
confidence: 99%
“…The only chloro-substituted Cii-progestational steroid to have been widely used is chlormadinone acetate (II) (Ringold et al, 1959;Brückner et al, 1961). Its metabolism in women has been investigated (Bermudez et al, 1968), but the identity of its metabolites has not been reported.…”
mentioning
confidence: 99%